PENGEMBANGAN LKPD BERBASIS STEAM PADA MATERI LARUTAN PENYANGGA - Siregar, Peni Rahmadani; Mauliza; Oktaviani, Coryna (Universitas Samudra, 2024)
This research is motivated by the large use of textbooks as teaching materials, where teachers rely on textbooks without utilizing teaching materials to support the success of the teaching and learning process. This study aims to determine the need, feasibility, practicality, and attractiveness of STEAM-based worksheets on the developed buffer solution material. This research is development research, the method used in this research is the Research and Development (R & D) method with the ADDIE model, analysis, desaigh, development, implementation, and evaluation. However, the implementation and evaluation stages were not carried out. The research instrument used was a questionnaire consisting of needs analysis sheets, material and media feasibility, practicality and attractiveness. The feasibility of the media and material was validated by validators, namely 2 chemistry education lecturers at Samudra University, practicality was assessed by 5 chemistry teachers at SMAN 2, 4, and 5 Langsa, and attractiveness was assessed by 30 students at SMAN 2, 4, and 5. Feasibility validity data were analyzed using the Aiken's V formula, while teacher and student responses were analyzed using a Likert scale. The results of the study showed that chemistry teachers needed STEAM-based worksheets on buffer solution material. The STEAM-based LKPD Feasibility Questionnaire developed obtained an average percentage of Aiken's V of 0.76% with a valid category. Teacher response questionnaires on STEAM-based LKPD are in very practical criteria with an average score of 92.5% and student response questionnaires get an average score of 97%. So it can be concluded that the STEAM-based LKPD developed is suitable for use in learning.